IoT BASED AUTOMATIC VEHICLE ACCIDENT DETECTION AND RESCUE SYSTEM - BAHROM, ARIF HAZMAN (IRC, 2019)
Every day, many lives are badly injured or lost due to road accidents on roads. Most of the time, heavy injuries on the passenger that occurred during the accident can lead to death, but injuries, even the worst ones can be attended to which could save the victim’s life. However, it usually takes a lot of time for the authorities to reach an accident mostly due to traffic and information on the accident is usually called in by other people who witnessed the accident. These causes the authorities to delay their actions to try to save the victims due to the layered communication. The delay in communications causes ambulance reaching the site of the accident a bit late where the longer the time it takes for the ambulance to arrive, the higher the chances of death to occur. To avoid this, every car must have an automatic system which not only detect a road accident efficiently but can also notify it to the emergency department and authorities nearby immediately.